The Type VI secretion system in commensal Neisseria spp. Issue 7 (10th July 2020) - Calder, Alan; Snyder, Lori
Abstract : A type 6 secretion system (T6SS) was recently identified in the genome sequence data of an isolate sourced from a throat swab of a volunteer that is believed to be N. subflava . The T6SS is one of the most recently discovered bacterial secretion systems and this is the first time it has been reported in Neisseriaceae . Since this discovery, genome sequence analyses for a number of other commensal Neisseria spp. has identified that in fact, two distinct T6SS types exist across Neisseriaceae . These two types are clearly defined and are different to one another in both their core gene sequences and organisation. The two systems also differ in the number of VgrG proteins required for toxic effector protein delivery, as well as type of effector associated with them. The predicted VgrG/effector combinations identified in our isolate are not common to all members of the same species and further analysis has identified a wide range of diversity in these components between different strains of the same species. The data provides possible evidence that T6SS positive commensal Neisseria spp. can acquire new VgrG/effector combinations through competitor killing. A number of putative effectors have so far been identified within the genome of our original isolate, including hydrolases, phospholipases, and nucleases. Whilst these are predicted to be antibacterial effectors, the conditions under which the T6SS system is activated, as well as demonstration of the function of the effectors still needs to be investigated experimentally.